Textured and Smooth Implant Use Reported in the Tracking Operations and Outcomes for Plastic Surgeons Database: Epidemiologic Implications for BIA-ALCL - Evan Matros, MD, MMSc, MPH; Meghana G. Shamsunder, MPH; Robyn N. Rubenstein, MD; Thais O. Polanco, MD; Colleen M. McCarthy, MD, MS; Jonas A. Nelson, MD, MPH; Karol Gutowski, MD; The TOPS Steering Committee (Plastic and Reconstructive Surgery, Global Open, 2021)
Background:. Breast-implant–associated anaplastic large cell lymphoma (BIA-ALCL) is associated with prolonged exposure to textured implants. Current studies describing textured implant use are limited to single center/surgeon experiences. Using the Tracking Operations and Outcomes for Plastic Surgeons database, the study aims to characterize national trends in rates of smooth versus textured implant utilization. The hypothesis is that rates of textured implant use have decreased in the most recent time period. Methods:. Tracking Operations and Outcomes for Plastic Surgeons was queried from 2007 to 2019 for CPT codes involving breast implant use in augmentation and reconstruction. The rate of smooth and textured implant utilization was calculated for each year per procedure type. Generalized additive models with a smoothing function and Pearson chi-square tests were used to assess the trends. Results:. Textured implant use peaked in 2016, being utilized in 17.83% of cosmetic and 40.88% of reconstructive procedures. Textured implants were more commonly used for reconstructive compared with cosmetic cases for 2007–2009, 2011, and 2013–2019 (P < 0.02). Both cosmetic and reconstructive cases had nonlinear trends in textured implant use over the study period, with textured rates decreasing from 2017 to 2019 (P < 0.001). In 2019, textured implants were used in 2.15% of cosmetic and 7.58% of reconstructive cases. Conclusions:. This is the first national study describing trends in textured versus smooth breast implant use in the United States. Textured implant utilization peaked in 2016. Based on a median time horizon of 10 years before development of BIA-ALCL, the peak number of cases can be anticipated in 2026 or thereafter.